Behavior of composite sandwich panel under quasi-static indentation load [electronic resource] - Arash Izadi Jajarm, 1984- (2014)
Thesis (Sarjana Kejuruteraan (Kejuruteraan Industri)) - Universiti Teknologi Malaysia, 2014